2006
DOI: 10.1182/blood-2005-11-4429
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results and competing risk analysis of the H89 trial in patients with advanced-stage Hodgkin lymphoma: a study by the Groupe d'Etude des Lymphomes de l'Adulte (GELA)

Abstract: From 1989 to 1996, 533 eligible patients with stage IIIB/IV Hodgkin lymphoma (HL) were randomly assigned to receive 6 cycles of hybrid MOPP/ABV (mechlorethamine, vincristine, procarbazine, prednisone/Adriamycin [doxorubicin], bleomycin, vinblastine; n ‫؍‬ 266) or ABVPP (doxorubicin, bleomycin, vinblastine, procarbazine, prednisone; n ‫؍‬ 267). Patients in complete remission (CR) or partial response of at least 75% after 6 cycles received 2 cycles of consolidation chemotherapy (CT) (n ‫؍‬ 208) or subtotal nodal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 29 publications
(33 reference statements)
0
19
0
4
Order By: Relevance
“…Nonetheless, approximately 40% of patients are refractory to initial treatment and/or relapse after achieving complete remission. 1,2 Various prognostic systems are currently used to predict the outcome of cHL patients, including the International Prognostic Score (IPS), which is considered the "gold standard" for advancedstage patients. 3 However, the IPS has limited applicability for early-stage patients.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, approximately 40% of patients are refractory to initial treatment and/or relapse after achieving complete remission. 1,2 Various prognostic systems are currently used to predict the outcome of cHL patients, including the International Prognostic Score (IPS), which is considered the "gold standard" for advancedstage patients. 3 However, the IPS has limited applicability for early-stage patients.…”
Section: Introductionmentioning
confidence: 99%
“…Лучевая консолидация не улучшила результатов лечения больных в полной ремиссии ЛХ, получивших 6 или 8 циклов ABVD, но потенциально повысила эффективность его у пациентов с частичной ремиссией [7,8]. Эти данные подтверждает и рандо-мизированное контролируемое исследование UK Lymphoma Group LY09.…”
Section: Introductionunclassified
“…49,50 A randomized EORTC study 44 demonstrated that consolidation with IF-RT did not improve the outcome in patients in complete remission after 6-8 courses of alternating MOPP and ABV, and a randomized GELA trial 45 that consolidation with IF-RT was not superior to two additional cycles of chemotherapy. The EP concluded that in patients achieving complete remission with chemotherapy, additional radiotherapy does not improve the overall results.…”
Section: The Role Of Rtmentioning
confidence: 99%
“…To reach their conclusions, the experts have analyzed the results of randomized clinical trials, either as full papers [33][34][35][36][37][38][39][40][41][42][43][44][45] or abstracts, [46][47][48] and of meta-analyses of randomized clinical trials. 49,50 Evidence for the efficacy of chemotherapy to cure advanced Hodgkin's lymphoma has derived from studies initiated more than 35 years ago, with the introduction into the clinical practice of MOPP (mechlorethamine, vincristine, procarbazine, prednisone) chemotherapy.…”
Section: First-line Therapy For Advanced Stage Diseasementioning
confidence: 99%